Caracterização dos padrões de recombinação das principais subpopulações globais de begomovírus - Gontijo, Ana Paula Ferreira Pinheiro (2019)
Populations of plant viruses show high levels of genetic variability due to the evolutionary mechanisms of mutation, recombination and pseudorecombination. As a consequence, viral populations evolve rapidly being able to expand their host ranges and overcome the genetic resistance of plants at a faster rate than populations of other disease-causing agents. Begomoviruses (genus Begomovirus, family Geminiviridae) are highly prone to both intra and interspecific recombination. In fact, several recently published studies indicate that most of the known begomovirus species have a recombinant origin. On the other hand, due to the geographical isolation of begomovirus subpopulations, it is possible that the recombination affects each one in a different extent. In this context, the present study aimed to characterize the recombination patterns in each of the major subpopulations that composes the begomovirus global metapopulation. For this, genomic sequences of begomovirus isolates collected in different locations around the world were obtained from Genbank database and analyzed using computational tools of population genetics. The metapopulation was subdivided into two to eight major subpopulations using a multivariate statistical-based approach. The sequences corresponding to the isolates of each subpopulation were analyzed for the presence and distribution of recombination breakpoints. The results obtained in this study indicate that the major begomovirus subpopulations show distinct recombination dynamics, with an evolutionary isolation determined by their geographic distribution.